Integrating Pesantren Heritage into Higher Education: A Cross-Case Study of Curriculum Design and Development at Ma’had Aly Sukorejo and Tebuireng - Maktumah, Luluk; Ni Wayan Suarniati; Wedi Samsudi; Salman Al Farisi (Mimbar Agama Budaya, 2025)
This research aims to explore the implementation of curriculum design and the applied curriculum development model in two Ma’had Aly institutions. Grounded in the theories of Allan C. Ornstein, Francis P. Hunkins, Jhon P. Miller, Wayne Seller, Robert S. Zais, and Richard A. Gorton, this study adopts a multi-case qualitative approach. Data were obtained through participant observation, in-depth interviews, and document analysis, and then processed using three stages: data reduction, data display, and conclusion drawing. The findings reveal two major contributions. First, the curriculum design integrates four models: subject-centered, learner-centered, problem-centered, and book-centered design. The inclusion of the book-centered model offers a critical addition to Ornstein and Hunkins' framework. Second, the curriculum development process reflects a hybrid between administrative and grassroots models, supported by four orientations: transmission, transaction, transformation, and transcendence. The transcendence orientation, overlooked by Miller and Seller, emerges as a distinctive value in pesantren education, emphasizing spiritual depth. These findings imply theoretical refinements, extending and correcting earlier models by incorporating pesantren-specific values. Thus, this study contributes significantly to the discourse on Islamic higher education by providing a contextualized and integrative curriculum framework that balances traditional pesantren heritage with contemporary educational paradigms.